A pre‐column derivatization high‐performance liquid chromatography method for simultaneous determination of short‐chain and medium‐chain fatty acids in a fecal sample. Issue 1 (3rd November 2022) - Fu, Zhibo; Zhang, Hongyang; Zeng, Zhijun; Ning, Fanghong; Xu, Ziwei; Liu, Chenyu; Zhang, Min; Hu, Ping
Abstract : Short‐chain and medium‐chain fatty acids have plentiful biological functions, which play a crucial role in the diagnosis and therapy of many diseases. Herein, a new method for simultaneous quantifying 17 short‐chain and medium‐chain fatty acids with high‐performance liquid chromatography coupled with an ultraviolet detector was developed and the pre‐column derivatization by indole‐3‐acetic acid hydrazide was performed to improve the separation and detection. The conditions of the derivatization reaction were systematically investigated. Subsequently, the method was validated and the results showed a satisfactory linearity (linear regression coefficients > 0.9969), the limit of detection (4.0×10 −3 –1.9×10 −2 μmol/L), precision (0.9%–7.3% for intra‐day and 2.0%–9.8% for inter‐day), recovery (90.0%–109.1% with relative standard deviation <7.7%) and stability (0.1%–3.3% for standard solution and 0.2%–3.9% for fecal sample). Finally, the established method was successfully applied to quantify short‐chain and medium‐chain fatty acids in the feces of healthy control and diabetic rats. Eleven kinds of short‐chain and medium‐chain fatty acids were detected and six of them showed a significant difference between the control group and the model group.